PENGEMBANGAN PROGRAM POSITIVE BEHAVIORAL SUPPORT (PBS) BERBASIS KELUARGA UNTUK MENGURANGI SELF-INJURY PADA ANAK PENYANDANG AUTISM SPECTRUM DISORDER (ASD) - Gusty Prayogo Aziz, - (2023)
Children with Autism Spectrum Disorder (ASD) have communication barriers so they have difficulty expressing their likes and dislikes towards something, as a result, children often do self-injury as a form of behavior that functions to convey messages. The child's behavior that often occurs is slapping the head which results in several injuries to the child's limbs. the family's response in handling children's behavior is by yelling, hitting and using locking techniques, but this method does not succeed in reducing the child's behavior in slapping his face. This study aims to reduce the self-injury behavior of children with Autism Spectrum Disorder (ASD) by using a family-based Positive Behavioral Support (PBS) program. The method used is a Research and Development design adapted from Sukmadinata with three stages: literature study to explore relevant previous theories and research, program development based on the results of assessments of children and families and testing using Single Subject Research (SSR). The program was developed in 3 settings where the most children did self-injury, namely when they were wearing clothes, listening to the call to prayer, and eating with their families. The program begins with training on family understanding of children with ASD, self-injury, as well as teaching intervention skills. Interventions carried out by parents are teaching substitute skills by teaching children to express what they want and what they don't want, teaching how to call to prayer and how to answer the call to prayer, providing additional visuals in the form of pictures to explain the context of clothing, placing cutlery in accessible areas children, separating children's food from others, responses to self-injury behavior in the form of rewards, giving the child's favorite perfume and giving praise for the child's success in following orders. The results showed that there was a significant change from the main level of baseline conditions (A1) to intervention (B1) which decreased in direction and overlap presentation of 0%. This shows that the use of family-based PBS programs has a good effect on reducing self-injury behavior in children with autism spectrum disorder.